Design and Implementation of a Low-cost MOSFET Based Chopper Drive DC Motor Speed Control - Bhuiyan, Mohammad Arif Sobhan (Journal of Science and Technology, 2017)
Electric drives have numerous applications in diverse areas such as rolling mills, electric trains and robotic manipulators. Inefficient control of motor speed can destroy the equipment itself; even can cause a severe accident. In this project, a low-cost MOSFET based chopper drive DC motor speed control system was designed and implemented. In this system, the feedback voltage from the load controls the speed of the DC motor through speed controller. From the measurement, it is clear that for a maximum rpm of 210, the percentage of error varied from 1.10 to 14.28 for 12 V supply voltage. The total cost of the speed control scheme is only 18 USD. Such a drive will be appropriate for the speed control of DC motor in household to industrial appliances.